Mark bevirʼs a theory of governance from the vantage of political philosophy. Issue 3 (1st March 2016) - Macleod, Colin
Abstract : This paper offers a critical commentary on Mark Bevirʼs recent book A Theory of Governance from the perspective of normative political philosophy. It explores three ways in which Bevirʼs analysis can be brought into dialogue with political philosophy. First, it considers the role of generalizations in successful explanations of social phenomena. Second, it explores how a decentred theory of governance can help identify solutions to important social problems. Third, it explores the relation between Bevirʼs account of governance and theories of deliberative democracy.